Orthodontic cements: immediate protection and fluoride release Cimentos ortodônticos: proteção imediata e liberação de flúor - Rogério Lacerda dos Santos; Matheus Melo Pithon; Júlia Barbosa Pereira Leonardo; Edna Lúcia Couto Oberosler; Delmo Santiago Vaitsman; Antônio Carlos de Oliveira Ruellas (Dental Press Editora, 2012)
OBJECTIVES: The objective of the authors was to evaluate fluoride release of 3 glass ionomer cements with immediate protection of fluoride varnish (Cavitine, SS White), divided into 3 groups: Group M (Meron, VOCO), Group V (Vidrion C, SS White) and Group KC (Ketac-Cem, 3M ESPE). METHODS: Fluoride release was measured during 60 days by means of an ion-selective electrode connected to an ion analyzer. After 4 weeks, the test specimens were exposed to a solution of 0.221% sodium fluoride (1000 ppm of fluoride). RESULTS: Results showed that the cements reached a maximum peak of fluoride release in a period of 24 h. There was a statistically significant difference between the amount of fluoride released after the applications of fluoride among the groups from the 31st to 60th day (p> 0.05). CONCLUSION: The Vidrion C and Meron cements showed better performance to uptake and release fluoride when compared with Ketac-Cem cement. OBJETIVO: o objetivo desse estudo foi avaliar a liberação de flúor dos seguintes três cimentos de ionômero de vidro, com proteção imediata de verniz fluoretado (Cavitine, S. S. White): Meron / VOCO (Grupo M); Vidrion C / S. S. White (Grupo V); e Ketac Cem / 3M ESPE (Grupo KC). MÉTODOS: a liberação de flúor foi medida durante 60 dias, através de eletrodo íon seletivo conectado a um analisador de íons. Após quatro semanas, os corpos de prova foram expostos a uma solução de fluoreto de sódio a 0,221% (1.000ppm de flúor). RESULTADOS: os resultados evidenciaram que os cimentos atingiram o pico máximo de liberação de flúor com 24h após a presa inicial. Houve diferença estatisticamente significativa entre os grupos, quanto à quantidade de flúor liberado após as aplicações de flúor, do 31º ao 60° dia (p > 0,05). CONCLUSÃO: os cimentos Meron e Vidrion apresentaram maior capacidade de captação e liberação de flúor, em comparação ao cimento Ketac Cem.